2020
DOI: 10.1021/acs.jafc.0c01681
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of the Opium Alkaloids Morphine, Codeine, and Thebaine in Poppy Seeds are Reduced after Thermal and Washing Treatments but are Not Affected when Incorporated in a Model Baked Product

Abstract: Limited information exists on the effectiveness of potential treatments to reduce levels of opium alkaloids that may be present in seeds from poppy (Papaver somniferum L.). Poppy seeds containing morphine at relatively lower (14.7 mg kg–1) and higher (210.0 mg kg–1) concentrations were subjected to dry heat and steam treatments, water washing, and baking. Sample extracts were then analyzed using liquid chromatography–tandem mass spectrometry for the opium alkaloids morphine, codeine, and thebaine. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 30 publications
3
44
2
1
Order By: Relevance
“…Due to moisture retained in dough throughout the baking process, it is important to monitor the temperature of the baked product, as there can be large differences between the set oven temperature and the surface/ interior of the baked product. In contrast to the conclusions made by Carlin et al, our group's research has found that baking poppy seeds either incorporated in a baked product (a muffin) or applied to the product's surface resulted in no significant effect on opium alkaloid levels (See Figure 1) (Shetge et al, 2020). The results from these baking experiments were supported by determining the activation energy (E a ) values and half-lives of the major opium alkaloids in poppy seeds, which showed relatively low thermal sensitivity of morphine and codeine.…”
contrasting
confidence: 82%
See 3 more Smart Citations
“…Due to moisture retained in dough throughout the baking process, it is important to monitor the temperature of the baked product, as there can be large differences between the set oven temperature and the surface/ interior of the baked product. In contrast to the conclusions made by Carlin et al, our group's research has found that baking poppy seeds either incorporated in a baked product (a muffin) or applied to the product's surface resulted in no significant effect on opium alkaloid levels (See Figure 1) (Shetge et al, 2020). The results from these baking experiments were supported by determining the activation energy (E a ) values and half-lives of the major opium alkaloids in poppy seeds, which showed relatively low thermal sensitivity of morphine and codeine.…”
contrasting
confidence: 82%
“…Although Carlin et al cites previous work that suggested baking conditions may significantly reduce levels of opium alkaloids in poppy seeds (Sproll et al, 2006), we have previously noted that such experiments were confounded by processing steps including soaking of the poppy seeds, which has been reported to reduce opium alkaloids on the surface of poppy seeds (Shetge et al, 2020). Also, analysis of opium alkaloids by mass spectrometry can be influenced by sample matrix (López et al, 2018), but it is unclear whether the referenced baking experiments used matrix-matched standards to control for such effects.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Due to its toxic effects above certain thresholds as well as the potential for confounding drug tests for opiates (Lachenmeier et al, 2010 ), this question is of significant importance regarding acceptable levels for products intended for baking purposes. While previous literature has generally assumed a considerable decrease of morphine and other alkaloids during baking (Brenneisen and Borner, 1985 ; Kniel, 2006 ; Sproll et al, 2006 , 2007 ; Carlin et al, 2020 ), new data from the U.S. Food and Drug Administration (FDA) (Shetge et al, 2020 ; also see discussion in Kleinmeier et al, 2021 ) has shed doubt on this opinion as opiate levels were quite stable when incorporated into a model baked product. Kleinmeier et al ( 2021 ) tried to explain this discrepancy by the possible confounding of previous baking experiments by processing steps including soaking of the poppy seeds, which has been reported to reduce opium alkaloids on the surface of poppy seeds.…”
mentioning
confidence: 99%